Divine violence and the character of God - Mariottini, Claudemiro Francisco 1942-; McKnight, Scot 1953- (Eugene, Oregon Wipf & Stock, 2022)
Scott McKnightDivine violence --Understanding divine violence --Dealing with divine violence --Divine violence and the suffering of God --Divine violence and divine pathos --The Character of God --Divine justice --The problem of idolatry --"The day I settle accounts" --The alien work of God --The genocidal God --The practice of ripping open pregnant women --The righteous judge and the fate of Sodom --Yahweh rejects violence --The nonviolent conquest of Canaan --The conquest of Canaan --God reconciling the world by himself --God reconciling the world through Israel --God reconciling the world through restored Israel --God reconciling the world through renewed Israel --
"There is much violence in the Old Testament, both human and divine. Christians and non-Christians react differently to what they read about the God of the Old Testament. Some people are so affected by the violence found in the Old Testament that they give up on God, stop going to church and reading the Bible, and eventually lose their faith. Others are offended by divine violence and seek to find an alternative explanation for the violent acts of God in the Old Testament. A popular alternative in the twenty-first century is to return to the second century and adopt some form of Marcionism and make the God of the Old Testament to be a different God from the God revealed by Christ in the New Testament. The purpose of this book is not a defense of God and his use of violence. The author seeks to understand why God acted the way he did and to understand the reason for divine violence in the Old Testament. Yahweh did use violence in his work of reconciliation. However, the use of violence was necessary when everything else failed. Israel provoked God to anger. When God brought judgment upon his people, he did so with tears in his eyes." -- Publisher's Description
Keywords: Bibel; Gewalt; Biblische Theologie; Eigenschaft Gottes